Silver influence of physical and thermo luminescence properties on lithium-Strontium-borate LSBO: Ag exposed to cobalt-60 gamma ray - Obayes, H. K. (Asian Research Publishing Network, 2016)
This work investigates the properties of glow curve of lithium Strontium borate doped sliver glass (LSBO: Ag), subjected to Co-60 gamma irradiation. The glass samples were prepared in different compositions based on 15%Li2CO3+2%SrCO3 (83-x) H3BO3 +xAgNO3, where x = 0.001, 0.003, 0.005, 0.007, 0.009 and 0.01 mol% by traditional melting quenching method at temperature 1300 °C for 1 hour. The structural pattern of glass samples has been identified by X-ray diffraction. The XRD pattern shows that the samples are glasses since there is broader peak appearing in the spectral pattern. FESEM images verify the homogeneous and transmitting surface morphology of all samples. Stable glasses with Hurby parameter ~ 0.5 are achieved. EDX spectra determine the accurate elemental compositions in the samples. Physical properties are determined in terms of glass density, molar volume, polar on radius, inter-nuclear distance, and ion concentration. Glass density is found to increase from 2.45 to 2.46 g cm-1 after addition of AgNO3 concentration. The TL intensity at different compositions of lithium borate doped sliver glass after exposed to 50 Gy Co-60 gamma-rays is presented. The results clearly show that the highest TL intensity is found in glass composition of 0.09 mol% of AgNO3.